Role of mean fetal kidney length as an additional parameter in late trimester for accurate estimation of gestational age relative to other biometrics indices - Sahay, Shalini; Sharma, Manju; Kumar, Devendra; Meena, Bhawar Singh (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: As biometric indices are difficult to obtain or show gross discrepancies with each other or with gestational age in the late trimester, so for accurate dating additional parameter is required. Fetal kidney length is easy to measure and appear reliable in previous studies. Methods: Well dated 121 antenatal women from 28 to 40 weeks of gestation with no obstetric or medical risk factors were recruited and kidney length is assessed in longitudinal scan and maximum length is taken. fetal kidney length derived gestational age compared with other biometrics indices gestational age. Results: Mean kidney length showed significant correlation (r=0.899, p<0.001 value) with increasing gestational age. Mean kidney length dated pregnancy within ±8.5 days. Conclusions: Fetal kidney length measurement correlated well with other routinely used parameters for the estimation of gestational age and can be used as an accurate parameter to date pregnancy in the late trimester.